Bowel Excretion of Technetium-(99m)L, L-Ethylene Dicysteine Masquerading as a Dilated Ureter in a Case of Pelvi-Ureteric Junction Obstruction: Case Report and Review - Goel, Prabudh (J Indian Assoc Pediatr Surg, 2019)
The treatment plan and the decision for surgery in a significant proportion of patients with pelvi-ureteric junction (PUJ) obstruction type of hydronephrosis are dependent on the findings of renal scintigraphy. We report a case of a 3.5-year-old girl with right-sided PUJ obstruction, wherein the tracer excretion into the cecum and ascending colon complicated the clinical picture thereby misleading the final diagnosis or treatment plan and blurring the distinction between hydronephrosis and hydroureteronephrosis. Additional investigations may be required in such cases to reach a conclusion. The authors considered reporting this case in view of the deep-rooted clinical implications toward making a correct diagnosis. Besides, the possible mechanisms to explain the presence of the tracer inside the bowel have been discussed.